Acute Liver Failure due to Hepatitis A Virus - Reem Shammout (Karger Publishers, 2021)
Acute liver failure (ALF) is a syndrome, rather than a specific disease, with several possible causes, and viral hepatitis is a major cause. The relationship between self-limited and ALF hepatitis A is still poorly understood. A 45-year-old woman presented to our hospital with ALF diagnosis (from another hospital). She suffered from hospital-acquired pneumonia. The patient recovered within 4 weeks and returned to her normal life after 6 months of follow-up.